2022
DOI: 10.2478/jesm-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Competence – a key competence for higher education

Abstract: Intercultural competence is an increasingly debated subject, at least in foreign specialized literature, not in the national one, especially in the context of university education where most exchanges of experience take place between universities from various European countries and not only. The purpose of this article is to identify and clarify from a theoretical point of view the concept of intercultural competence and the importance of its formation at the level of university education. The article analyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…It depends on the individual student's choices and the availability of resources. Many universities and colleges offer special courses in digital competencies development, graphic design, where students can learn how to use certain digital tools or learn how to work with Adobe editors and other tools (Marner & Örtegren, 2014;Matei, 2022). Adobe also provides online resources and trainings for users of its products, where students can gain practical skills in using Photoshop, Illustrator, and InDesign.…”
Section: Research Resultsmentioning
confidence: 99%
“…It depends on the individual student's choices and the availability of resources. Many universities and colleges offer special courses in digital competencies development, graphic design, where students can learn how to use certain digital tools or learn how to work with Adobe editors and other tools (Marner & Örtegren, 2014;Matei, 2022). Adobe also provides online resources and trainings for users of its products, where students can gain practical skills in using Photoshop, Illustrator, and InDesign.…”
Section: Research Resultsmentioning
confidence: 99%
“…The analysis of general development trends and specific training programs in European universities has shown that innovative teaching technologies function at the stages of formation, assimilation and implementation. The training of higher education students in pedagogy and psychology will require students to acquire professional and integral competencies (Matei, 2022) -based on all of the above formulas. First of all, it is about content, organisational, functional, and communicative competencies (Bondar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%